Effects of simulated acid rain on Shorea macroptera growth and selected soil chemical properties - Ibrahim, Mohamad Hilmi; Kasim, Susilawati; Ahmed, Osumanu Haruna; Nik Abd Majid, Nik Muhamad (Academic Journals, 2013)
There is dearth of information on the effect of acid deposition on Shorea macroptera in Malaysia. Thus, this study was conducted to investigate the potential effect of simulated acid rain (SAR) on S. macroptera growth and selected soil chemical properties. Six treatments were evaluated in this study. Growth variables of S. macroptera were observed for 90 days. After 90 days, seedlings and soil were sampled and analyzed using standard methods. The seedlings height decreased with decrease in SAR pH. Chlorosis and necrosis were observed for low SAR pH (pH 3.5 and 4) treatments and this observation explains the reduction of dry matter production of the plants subjected to these treatments. Regardless of treatment, K, Ca, Mg and Na contents in the plants and soil were statistically similar. A similar observation was found for soil exchangeable Fe, Cu, Zn, acidity, Al and H. Thus, it can be concluded that SAR pH of 3.5, 4 and 4.5 affects S. macroptera height, biomass and selected nutrient contents in soil. S. macroptera is susceptible to acid deposition and it could be considered as one of the bio-indicators in Malaysia. A field study is recommended to validate the findings of this study.